Electrode active material particle, electrode mixture, and lithium ion battery
By introducing specific proportional control of silicon-encapsulated crystals and amorphous silicon into the electrode active material, the problem of charging and expansion of silicon-based electrode materials is solved, achieving higher ionic conductivity and more stable battery performance.
Patent Information
- Application Number
- JP2023123369
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
Smart Images

Figure 2025019649000001_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to electrode active material particles, an electrode binder, and a lithium ion battery.
Background Art
[0002] In recent years, battery development has been actively carried out. For example, in the automotive industry, the development of batteries used in electric vehicles or hybrid vehicles has been advanced. Further, silicon is known as an electrode active material used in batteries, particularly lithium ion batteries.
[0003] Silicon electrode active materials have a large theoretical capacity and are effective for increasing the energy density of batteries. On the other hand, silicon electrode active materials have a problem of large expansion during charging. In contrast, it is known that the expansion during charging can be suppressed by using a silicon class rate electrode active material as the silicon electrode active material.
[0004] For example, Patent Document 1 discloses a silicon class rate electrode active material having a crystalline phase of silicon class rate type II and having a composition of Na x Si 136 (1.98 < x < 2.54).
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0006] Although the silicon class rate electrode active material can suppress expansion during charging as compared with a normal silicon electrode active material, it is required to further suppress the expansion during charging of the silicon class rate electrode active material.
[0007] An object of the present disclosure is to provide electrode active material particles that undergo small expansion during charging, and a lithium ion battery having such electrode active material particles. [Means for solving the problem]
[0008] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> Electrode active material particles comprising a silicon clathrate portion and an amorphous silicon portion, and satisfying the following relationship: 0 atom%<number of silicon atoms in the amorphous silicon portion / (number of silicon atoms in the amorphous silicon portion+number of silicon atoms in the silicon clathrate portion)<50 atom%. <Aspect 2> Electrode active material particles according to embodiment 1, which satisfy the following relational formula: 0 atom%<number of silicon atoms in the amorphous silicon portion / (number of silicon atoms in the amorphous silicon portion+number of silicon atoms in the silicon clathrate portion)≦30 atom%. <Aspect 3> An electrode mixture comprising the electrode active material particles according to embodiment 1 or 2. <Aspect 4> An electrode active material layer is provided, and The electrode active material layer contains the electrode mixture according to aspect 3. Lithium-ion battery. Effect of the Invention
[0009] According to the present disclosure, it is possible to provide electrode active material particles that expand little during charging, and a lithium ion battery having such electrode active material particles. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional TEM image of an electrode active material particle of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.
[0012] 《Electrode active material particles》 The electrode active material particles of the present disclosure include a silicon clathrate portion and an amorphous silicon portion, and satisfy the following relationship: 0atom%<number of silicon atoms in amorphous silicon portion / (number of silicon atoms in amorphous silicon portion + number of silicon atoms in silicon clathrate portion)<50atom%.
[0013] Silicon clathrate particles have a small change in expansion rate due to charging and discharging, but are highly sensitive to reaction unevenness, and the expansion rate increases as the reaction unevenness progresses. In this regard, the present inventors believe that the low ionic conductivity of silicon clathrate particles is the cause of this reaction unevenness. Specifically, without intending to be bound by any theory, it is believed that the reaction is concentrated on the particle surface due to the low ionic conductivity of silicon clathrate, which causes the reaction unevenness to progress.
[0014] In response to this, the present inventors have discovered that by making the silicon electrode active material particles contain a silicon clathrate portion and an amorphous silicon portion with high ionic conductivity, it is possible to prevent uneven reaction from progressing within the active material particles, thereby suppressing an increase in the expansion rate.
[0015] In the present disclosure, the "electrode active material" can be used as either a "positive electrode active material" or a "negative electrode active material", and is particularly used as a "negative electrode active material".
[0016] The electrode active material particles of the present disclosure include a silicon clathrate portion and an amorphous silicon portion.
[0017] The electrode active material particles of the present disclosure satisfy the following relational formula: 0atom%<number of silicon atoms in amorphous silicon portion / (number of silicon atoms in amorphous silicon portion + number of silicon atoms in silicon clathrate portion)<50atom%.
[0018] The number of silicon atoms in the amorphous silicon portion / (number of silicon atoms in the amorphous silicon portion+number of silicon atoms in the silicon clathrate portion) may be 0.10 atom% or more, 0.30 atom% or more, 0.50 atom% or more, 0.70 atom% or more, 0.80 atom% or more, 0.90 atom% or more, or 0.95 atom% or more, and may be 45 atom% or less, 40 atom% or less, 35 atom% or less, 30 atom% or less, 25 atom% or less, 20 atom% or less, 15 atom% or less, 10 atom% or less, 5.0 atom%, 3.0 atom% or less, or 1.0 atom% or less.
[0019] A method for quantifying the silicon clathrate portion and the amorphous silicon portion in the electrode active material particles includes a method using a crystal orientation analysis system (ASTAR) attached to a transmission electron microscope (TEM). More specifically, the silicon clathrate portion and the amorphous silicon portion in the electrode active material particles can be quantified by continuously collecting diffraction patterns while scanning an electron beam probe on a sample using ASTAR manufactured by Nanomegas.
[0020] The ionic conductivity of the electrode active material particles may be greater than 0.066 mS / cm, and may be 0.067 mS / cm or more, 0.068 mS / cm or more, or 0.069 mS / cm or more, and may be 0.100 mS / cm or less, 0.090 mS / cm or less, 0.085 mS / cm or less, or 0.080 mS / cm or less.
[0021] This ionic conductivity can be measured by the following method. That is, first, a confining pressure is applied to a pellet obtained by pressing the electrode active material particles. Then, the obtained sample is kept at 25°C and the ionic conductivity is calculated by an AC impedance method. For the measurement, a Solartron 1260 manufactured by Solartron Analytical can be used. The measurement conditions can be an applied voltage of 5 mV and a measurement frequency range of 0.01 to 1 MHz.
[0022] Examples of methods for producing the electrode active material particles of the present disclosure include, but are not limited to, a method including mixing a silicon raw material and a sodium source and heating to form an alloy, thereby obtaining a powdered sodium silicon (NaSi) alloy, and mixing the obtained NaSi alloy with aluminum fluoride and heating to form a clathrate, thereby obtaining a silicon clathrate.
[0023] The sodium source in the alloying step can be exemplified by, but is not limited to, sodium hydride.
[0024] The heating temperature in the alloying step may be 350° C. or more, 400° C. or more, or 450° C. or more, and may be 650° C. or less, 600° C. or less, or 550° C. or less.
[0025] The heating temperature in the clathration step may be 200° C. or more, 250° C. or more, or 270° C. or more, and may be 400° C. or less, 350° C. or less, or 330° C. or less.
[0026] The ratio of the silicon clathrate portion and the amorphous silicon portion in the obtained electrode active material particles can be controlled by adjusting the heating temperature in the alloying step and the clathrating step, by using aluminum fluoride of a predetermined particle size in the clathrating step, etc. Furthermore, this ratio can also be controlled by charging the obtained electrode active material particles.
[0027] The silicon clathrate portion in the electrode active material of the present disclosure may be a porous silicon clathrate. The porous silicon clathrate can absorb expansion due to charging and discharging by its voids.
[0028] Examples of methods for producing the electrode active material particles of the present disclosure when the silicon clathrate portion is a porous silicon clathrate include, but are not limited to, a method including mixing silicon and metallic lithium to obtain a lithium silicon (LiSi) alloy, reacting the obtained LiSi alloy with ethanol to obtain porous silicon, and using the obtained porous silicon as a silicon raw material to obtain a silicon clathrate as described above.
[0029] 《Electrode composite material》 The electrode mix of the present disclosure includes electrode active material particles. The electrode mix of the present disclosure optionally contains a solid electrolyte, a conductive additive, and a binder.
[0030] <Electrode active material particles> For the electrode active material particles, reference can be made to the above description regarding the electrode active material particles of the present disclosure.
[0031] <Solid electrolyte> The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for use in lithium ion batteries can be used. For example, the solid electrolyte may be a sulfide solid electrolyte.
[0032] Examples of sulfide solid electrolytes include, but are not limited to, sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.
[0033] The sulfide solid electrolyte may be a glass or a crystallized glass (glass ceramic).
[0034] <Conductive assistant> The conductive assistant is not particularly limited. For example, the conductive assistant may be VGCF (Vapor Grown Carbon Fiber), acetylene black (AB), Ketjen Black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.
[0035] <binder> The binder is not particularly limited. For example, the binder may be a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), or styrene butadiene rubber (SBR), or a combination thereof, but is not limited thereto.
[0036] In the present disclosure, the term "electrode mixture" refers to a composition that can constitute an electrode active material layer as it is or by further containing other components. In the present disclosure, the term "electrode mixture slurry" refers to a slurry that contains a dispersion medium in addition to the "electrode mixture" and can be applied and dried to form an electrode active material layer.
[0037] Lithium-ion battery The lithium ion battery of the present disclosure may be a liquid battery or a solid-state battery. In the present disclosure, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. The solid-state battery of the present disclosure may also be an all-solid-state battery, i.e., a battery that uses only a solid electrolyte as an electrolyte.
[0038] The lithium ion battery of the present disclosure can be restrained from both sides of the stacking direction of each of the layers by restraining members such as end plates. Examples of the restraining method include, but are not limited to, a method that utilizes the restraining torque of a bolt.
[0039] The lithium ion battery of the present disclosure has an electrode active material layer, and the electrode active material layer contains the electrode mixture of the present disclosure. In particular, the lithium ion battery of the present disclosure may have a negative electrode mixture which is the electrode mixture of the present disclosure, and in this case, may include, in this order, a negative electrode current collector layer, a negative electrode active material layer containing the electrode mixture of the present disclosure, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer.
[0040] <Negative electrode current collector layer> The material used for the negative electrode current collector layer is not particularly limited, and any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, the material may be copper, a copper alloy, or copper plated or vapor-deposited with nickel, chromium, carbon, or the like, but is not limited to these.
[0041] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0042] <Negative electrode active material layer> The negative electrode active material layer contains the electrode mixture of the present disclosure. For the electrode mixture, reference can be made to the above description of the electrode mixture of the present disclosure.
[0043] When the negative electrode active material layer contains a solid electrolyte, the mass ratio of the electrode active material particles to the solid electrolyte in the negative electrode active material layer (mass of electrode active material particles:mass of solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 40:60.
[0044] The negative electrode active material layer may have a thickness of, for example, 0.1 to 1000 μm.
[0045] <Solid electrolyte layer> The solid electrolyte layer includes at least a solid electrolyte. In addition to the solid electrolyte, the solid electrolyte layer may include a binder, etc., as necessary. For the solid electrolyte and the binder, the above description regarding the electrode mixture of the present disclosure can be referred to.
[0046] The thickness of the solid electrolyte layer is, for example, 0.1 to 300 μm, and preferably 0.1 to 100 μm.
[0047] <Cathode active material layer> The positive electrode active material layer is a layer containing a positive electrode active material, and optionally a solid electrolyte, a conductive assistant, a binder, a thickener, and the like.
[0048] The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y Li-Mn spinel substituted with different elements, which has a composition represented by MyO4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), and lithium titanate (Li x TiO y ), lithium metal phosphate (LiMPO4, M is one or more metals selected from Fe, Mn, Co, and Ni), and the like, but are not limited thereto.
[0049] The positive electrode active material may have a coating layer. The coating layer is a layer containing a substance that has lithium ion conductivity, is low in reactivity with the positive electrode active material and the solid electrolyte, and can maintain the shape of the coating layer without flowing even when it comes into contact with the active material and the solid electrolyte. Specific examples of materials constituting the coating layer include LiNbO3, Li4Ti5O 12 , Li3PO4, etc., but are not limited to these.
[0050] The shape of the positive electrode active material may be, for example, particulate. The average particle size (D50) of the positive electrode active material is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D50) can be calculated, for example, from measurements using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM).
[0051] For the solid electrolyte, the conductive assistant, and the binder, reference can be made to the above descriptions regarding the electrode mixture of the present disclosure.
[0052] When the positive electrode active material layer contains a solid electrolyte, the mass ratio of the positive electrode active material to the solid electrolyte in the positive electrode active material layer (mass of positive electrode active material: mass of solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 50:50.
[0053] The thickness of the positive electrode active material layer is, for example, 0.1 μm to 1000 μm, preferably 1 μm to 100 μm, and more preferably 30 μm to 100 μm.
[0054] <Positive electrode current collector layer> The material used for the positive electrode current collector layer is not particularly limited, and any material that can be used as a positive electrode current collector for a battery can be appropriately adopted. For example, SUS, nickel, chromium, gold, platinum, aluminum, iron, titanium, zinc, etc., and these metals plated or vapor-deposited with nickel, chromium, carbon, etc. may be used, but is not limited to these.
[0055] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred. EXAMPLES
[0056] Synthesis Example 1 Synthesis of Electrode Active Material Particles (Porous) As a silicon (Si) source, Si powder (Kojundo Kagaku, SIEPB32) was prepared. This Si powder and metallic lithium (Li) were weighed out in a molar ratio of Li / Si=4.0, and the weighed Si powder and Li were mixed in a mortar in an argon atmosphere to obtain a lithium silicon (LiSi) alloy. The obtained LiSi alloy was reacted with ethanol in an argon atmosphere and treated with hydrogen fluoride (HF) to obtain a Si powder having voids inside the primary particles, i.e., a Si powder having a porous structure.
[0057] (alloying) A sodium silicon (NaSi) alloy was produced using Si powder having a porous structure and sodium hydride (NaH) as a sodium (Na) source. The NaH used was washed with hexane in advance. NaH and Si powder were weighed out so that the molar ratio was 1.05:1, and the weighed NaH and Si powder having a porous structure were mixed in a cutter mill. The resulting mixture was heated in a heating furnace under an argon atmosphere at 500°C for 40 hours to obtain a powdered NaSi alloy.
[0058] (Clatification) The obtained NaSi alloy and aluminum fluoride (AlF3) particles were weighed to a molar ratio of 1:0.35, and the weighed NaSi alloy and AlF3 particles were mixed with a cutter mill to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction vessel, and reacted in a heating furnace under an argon atmosphere at 310°C for 60 hours to obtain a silicon clathrate. The obtained silicon clathrate was acid washed using a mixed solvent of HNO3 and H2O in a volume ratio of 10:90 to remove by-products in the reaction product. After washing, it was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain a powdered silicon clathrate. Furthermore, the obtained silicon clathrate was washed with a 3 wt% hydrogen fluoride (HF) solution, filtered, and then dried at 120°C for 3 hours or more to obtain electrode active material particles of Synthesis Example 1.
[0059] Comparative Synthesis Example 1 A NaSi alloy was obtained in the same manner as in Synthesis Example 1, except that in the alloying step, Si powder (Kojundo Kagaku, SIEPB32) was used, i.e., porous silicon was not prepared before the alloying step, and heating was performed under conditions of 700°C and 20 hours. The obtained NaSi alloy was heated in a heating furnace in an argon atmosphere at 340°C to form a clathrate, and further pulverized in a ball mill (manufactured by Fritsch), to obtain electrode active material particles of Comparative Synthesis Example 1.
[0060] Comparative Synthesis Example 2 Metallic lithium (Li) and Si powder (Kojundo Kagaku, SIEPB32) were weighed out to a molar ratio of 4:1, and were mixed in a mortar under argon atmosphere at room temperature for 0.5 hours to react with each other. Li4Si was obtained. The Li4Si obtained was reacted with ethanol under argon atmosphere. The reaction product was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain powdered porous silicon. The porous silicon was washed with a 3 wt% HF solution, filtered, and then dried at 120°C for 3 hours or more to obtain electrode active material particles of Comparative Synthesis Example 2.
[0061] Comparative Synthesis Example 3 Electrode active material particles of Comparative Synthesis Example 3 were obtained in the same manner as in Synthesis Example 1, except that clathration was carried out using AlF3 pulverized by a ball mill.
[0062] The surface of the electrode active material particles in each example may contain a coating or impurities containing O, C, N, or the like.
[0063] Example 1 (Making a lithium-ion battery) (Preparation of negative electrode mixture) Butyl butyrate, a 5 wt% butyl butyrate solution of polyvinylidene fluoride (PVDF) binder, vapor grown carbon fiber (VGCF) as a conductive assistant, electrode active material particles of Synthesis Example 1, and Li2S-P2S5 glass ceramic as a sulfide solid electrolyte were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersing device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.) to obtain a slurry-like negative electrode mixture (negative electrode mixture slurry).
[0064] (Formation of negative electrode active material layer) The obtained negative electrode composite slurry was applied onto a copper (Cu) foil serving as a negative electrode current collector layer by the blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C to form a negative electrode active material layer on the negative electrode current collector layer.
[0065] (Formation of solid electrolyte layer) Heptane, a 5 wt% heptane solution of butylene rubber (BR)-based binder, and Li2SP2S5-based glass ceramic as a sulfide solid electrolyte were added to a polypropylene container and stirred for 30 seconds with an ultrasonic disperser (UH-50, manufactured by SMT Co., Ltd.). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.) to obtain a solid electrolyte slurry.
[0066] The obtained solid electrolyte slurry was applied onto an aluminum (Al) foil as a release sheet by a blade method using an applicator, and dried for 30 minutes on a hot plate heated to 100°C to form a solid electrolyte layer. Multiple solid electrolyte layers were produced.
[0067] (Preparation of Positive Electrode Mixture) A polypropylene container is filled with butyl butyrate, a 5 wt% butyl butyrate solution of a PVDF-based binder, and LiNi with an average particle size of 6 μm as the positive electrode active material. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2S-P2S5-based glass ceramic as a sulfide solid electrolyte, and VGCF as a conductive additive were added to the container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was shaken for 3 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), further stirred for 30 seconds with the ultrasonic dispersion device, and shaken for 3 minutes with the shaker to obtain a slurry-like positive electrode mixture (positive electrode mixture slurry).
[0068] (Formation of Positive Electrode Active Material Layer) The obtained positive electrode mixture slurry was applied onto an Al foil serving as a positive electrode current collector layer by a blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C, thereby forming a positive electrode active material layer on the positive electrode current collector layer.
[0069] (Battery Assembly) The positive electrode current collector layer, the positive electrode active material layer, and the first solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 100 kN / cm and a temperature of 165° C. to obtain a positive electrode laminate.
[0070] The negative electrode current collector layer, the negative electrode active material layer, and the second solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 60 kN / cm and a temperature of 25° C. to obtain a negative electrode laminate.
[0071] Furthermore, the Al foil as a release sheet was peeled off from the surfaces of the solid electrolyte layers of the positive electrode laminate and the negative electrode laminate, and then the Al foil as a release sheet was peeled off from the third solid electrolyte layer.
[0072] The positive electrode laminate and the negative electrode laminate were laminated on each other so that the solid electrolyte layer side of each laminate faced the third solid electrolyte layer, and the laminate was set in a flat uniaxial press and pre-pressed at 100 MPa and 25° C. for 10 seconds, and finally the laminate was set in a flat uniaxial press and pressed for 1 minute at a pressing pressure of 200 MPa and a pressing temperature of 120° C. In this way, the all-solid-state battery of Example 1 was obtained.
[0073] Example 2 The negative electrode active material layer formed in the same manner as in Example 1 was laminated on the solid electrolyte layer, and a charge / discharge test was performed 200 times using lithium as the counter electrode under the condition of 3.17 V to 4.16 V. Thereafter, the negative electrode active material layer was removed, and this negative electrode active material layer, a new solid electrolyte layer, and a positive electrode active material layer were laminated in the same manner as in Example 1 to obtain an all-solid-state battery of Example 2.
[0074] Comparative Examples 1 to 3 All-solid-state batteries of Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that in the preparation of the negative electrode mixture, the electrode active material particles of Comparative Synthesis Examples 1 to 3 were used. Note that the numbers of each Comparative Example correspond to the numbers of the Comparative Synthesis Examples.
[0075] "evaluation" <Taking cross-sectional TEM images of electrode active material particles and quantifying each silicon portion> The cross section of the electrode active material particles of Example 1 was imaged by TEM. In addition, the silicon clathrate portion and the amorphous silicon portion in the electrode active material particles were quantified by ASTAR attached to the TEM. Specifically, each silicon portion was quantified by continuously collecting diffraction patterns while scanning the sample with an electron beam probe using ASTAR manufactured by Nanomegas.
[0076] <Measurement of ionic conductivity> The ionic conductivity of the electrode active material particles was measured by the following method. That is, first, a confining pressure was applied to a pellet obtained by pressing the electrode active material particles. Then, the obtained sample was kept at 25°C and calculated by an AC impedance method. For the measurement, a Solartron 1260 from Solartron Analytical was used. The measurement conditions were an applied voltage of 5 mV and a measurement frequency range of 0.01 to 1 MHz.
[0077] <Measurement of increase in confining pressure> The cell prepared using the restraining tool was restrained at a predetermined restraining pressure, and the restraining pressure increase was measured when the cell was charged at a constant current and constant voltage up to 4.55 V at a 10-hour rate (1 / 10C). A large restraining pressure increase means that the active material has a large expansion amount. The restraining pressure increase is the difference between the maximum and minimum restraining pressures, and the values of the example and comparative examples 2 and 3 are shown as relative values when the value of comparative example 1 is set to 100.
[0078] "result" 1 shows a cross-sectional TEM image of the electrode active material particles of Example 1. Table 1 also shows the measurement results of the ratio of the number of silicon atoms in each silicon portion, the ionic conductivity of the electrode active material particles, and the increase in the confining pressure of the battery.
[0079] [Table 1]
[0080] As shown in Figure 1, the electrode active material particles of Example 1 contained a silicon clathrate portion and an amorphous silicon portion in the particles. Also, as shown in Table 1, the battery of the Example containing the electrode active material particles of the present disclosure had a smaller increase in confining pressure than the battery of the Comparative Example. This is believed to be because the electrode active material particles of the present disclosure contain a silicon clathrate portion that has a high expansion coefficient suppression effect, and contain an amorphous silicon portion within the range of the present disclosure, thereby increasing the ion conductivity.
Claims
1. Electrode active material particles comprising a silicon clathrate portion and an amorphous silicon portion, and satisfying the following relational formula: 0 atom %<the number of silicon atoms in the amorphous silicon portion / (the number of silicon atoms in the amorphous silicon portion+the number of silicon atoms in the silicon clathrate portion)<50 atom %.
2. The electrode active material particles according to claim 1 , which satisfy the following relational formula: 0 atom %<number of silicon atoms in the amorphous silicon portion / (number of silicon atoms in the amorphous silicon portion+number of silicon atoms in the silicon clathrate portion)≦30 atom %.
3. An electrode mixture comprising the electrode active material particles according to claim 1 or 2.
4. An electrode active material layer is provided, and The electrode active material layer contains the electrode mixture according to claim 3. Lithium-ion battery.
Citation Information
Patent Citations
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158003A